LOUGHBOROUGH UNIVERSITY, UK AFFIRMS RESEARCH COLLABORATION WITH USM - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 16 April 2016 – Loughborough University, United Kingdom has shown an interest in establishing research collaboration focusing in the field of engineering with Universiti Sains Malaysia (USM).